1996
DOI: 10.1136/gut.38.3.348
|View full text |Cite
|
Sign up to set email alerts
|

In vivo IgA coating of anaerobic bacteria in human faeces.

Abstract: The bacterial flora in the human colon, although extremely diverse, has a relatively stable composition and non-infectious anaerobic bacteria are dominant. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(132 citation statements)
references
References 28 publications
6
123
0
1
Order By: Relevance
“…Coating of bacteria has been previously observed in feces samples recovered from human and mouse (12,41), suggesting that this takes place at all times in the gut lumen. We made the assumption that nonspecific SIgA serving as substitute of natural SIgA can bind to commensals in a Fab-independent fashion.…”
Section: Siga Binds Bacteria In a Fab-and Fc-independent Manner-mentioning
confidence: 96%
See 2 more Smart Citations
“…Coating of bacteria has been previously observed in feces samples recovered from human and mouse (12,41), suggesting that this takes place at all times in the gut lumen. We made the assumption that nonspecific SIgA serving as substitute of natural SIgA can bind to commensals in a Fab-independent fashion.…”
Section: Siga Binds Bacteria In a Fab-and Fc-independent Manner-mentioning
confidence: 96%
“…The biological function of such SIgA remains speculative; however, various studies have underscored the natural coating of commensal bacteria by SIgA, a process that may be involved in the homeostatic gut sensing of the microbiota (12,41,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time course experiments showed that there is no dependence of the final concentration of bacteria on adhesion. 3 Because intestinal bacteria have been shown to be coated with a mixture of specific and nonspecific, "natural" SIgA (19,20), we sought to examine 3 B. Corthé sy, unpublished results. whether the combination of LPR and BL with SIgA might have influenced the adhesion properties of the bacteria.…”
Section: Adhesion Of Lpr Alone Bl Alone or In Complexes Withmentioning
confidence: 99%
“…However it has also been reported that commensal bacteria can elicit systemic antibody responses (Kimura et al, 1997). In addition a proportion of the resident microflora is covered by antibodies in the lumen of the gut, mainly of the IgA isotype (Van der Waaij et al, 1996).…”
Section: Interactions Between the Host And The Intestinal Microfloramentioning
confidence: 99%